Sacrificial animals as evidence for the disintegration of the ritual and music system: A case study of the Zhuolu site (790-410 BC) - Xin Yu; Hailin Liu; Zhe Zhang; Huiqiu Shao; Chunxue Wang; Dong Wei (PLoS ONE, 2025)
Ritual and music are important approaches to convey the ethical and moral concepts in the Zhou Dynasty (1046–256 BC) in China. The ritual and music (liyue) system, therefore, was established by the Duke of Zhou to maintain social order, create and strengthen the power of the Shang royalty. The essence of the system was the division of classes. The primary objective of this study was to analyze the sacrificial animals from the Zhuolu site (40°13´N, 115°24´E) in Hebei Province, China. We summarized the characteristics of sacrificial behavior during that period by examining the types of sacrificial animals and the specific parts of their bones. Ultimately, we discussed whether these characteristics align with the established rules of the ritual and music system. In this study, excavated animal bones were subjected to species identification, surface mark recording, and carbon and nitrogen stable isotope analyses. Skeletal surface marks and stable isotope analyses indicated that there are various methods by which people access and utilize animal resources. There are various animals, including pigs, deer, hares, ring-necked pheasants, and fish, were utilized in the burials. Included in these bones are not only the left and front parts of the body, but also the right part and the hind limbs. Not only is this inconsistent with the specified combination of animal species designated for sacrifice within the ritual and music system, but it also deviates from the requirement to utilize the left and front halves of the limbs. People may have changed and reduced the use of certain sacrificial animals according to their personal preferences and needs. This may be attributed to the disintegration of the ritual system during that period. By comparing different sites, it is possible to infer that the stringent execution of rules regarding the use of animals in burial rituals was directly related to the level of ritual system development during the period to which the site is associated.